Neuroimaging Features, Follow-Up Analyses, and Comparisons Between Asymptomatic and Symptomatic Neurosyphilis - Xian-Jin Shang; Cai-Feng He; Biao Tang; Xiao-Li Chang; Chao Ci; Hong Sang (Adis, Springer Healthcare, 2020)
Abstract Introduction Many studies have explored the imaging characteristics of patients with neurosyphilis, but no systematic study has been made on the neuroimaging changes after anti-syphilitic treatment. The purpose of this study was to examine neuroimaging differences before and after treatment, comparing patients with asymptomatic and symptomatic neurosyphilis. Methods A total of 102 patients with neurosyphilis, including 60 cases of symptomatic neurosyphilis and 42 cases of asymptomatic neurosyphilis, were identified between December 2012 and June 2019. Their demographics, medical histories, serological tests of peripheral blood and cerebrospinal fluid, and especially neuroimaging features before and after anti-syphilitic treatment were collected and analyzed. Results The patients presented with variable clinical and neuroimaging features, including cerebral infarction or hemorrhage, atrophy, demyelination, arteritis, encephalitis, and hippocampal sclerosis. A total of 29 neuroradiological re-examinations were performed in 19 patients treated with anti-syphilitic medicine. The results indicated that some patients still presented neuroradiological progression after treatment, including 42.1% showing infarction lesions, 47.4% mild to severe brain atrophy, and 15.8% white matter demyelination. Conclusion The clinical and neuroimaging features of neurosyphilis patients are diverse, and their follow-up neuroimaging continued to show progression even with standardized treatment.